Structure Optimization of Vibrating Feeder Based on Inertia Release - Ningning Xu; Xinwen Wang; Chi Yu; Sanpeng Gong; Dongdong Lin; Xing Su (Shock and Vibration)
Reliability is a key factor in the design and manufacture of vibrating feeders. In this paper, a method considering materials force was proposed to optimize the structure of the vibrating feeder. Discrete Element Method (DEM) was used to couple the materials force and the excitation force based on the phase characteristics of the vibrating feeder, and Finite Element Method (FEM) was used to analyze the vibrating feeder structure based on the inertia release method. In order to reduce the stress on the beam of the vibrating feeder, three structural improvement schemes were proposed, which were constructing a statically indeterminate structure, increasing the width of the rib-stiffened plates on the beam, and increasing the internal spacing of the beam. Then, these three schemes were compared using the FEM. Finally, the response surface method was used to optimize the width of the inner and outer rib-stiffened plates. The research results showed that when the vibrating feeder moved close to the highest point, the materials force reached the peak. The maximum first principal stress occurred at the middle and both ends of the vibrating feeder beam under the joint action of the excitation force and the materials force. The first principal stress value of the beam was most significantly decreased by increasing the width of the rib-stiffened plates on the beam of three optimization schemes. The optimal increment of rib-stiffened plate width was 30 mm with the maximum first principal stress value reduced by 40.12%.